2021
DOI: 10.1021/acs.macromol.0c02558
|View full text |Cite
|
Sign up to set email alerts
|

Thiophene-Fused Perylenediimide-Based Polymer Acceptors for High-Performance All-Polymer Solar Cells

Abstract: Over the past years, perylenediimide (PDI)-based polymers have emerged as one of the widely studied polymer acceptors applicable to all-polymer solar cells (PSCs) due to their outstanding photovoltaic properties. Covalently fused PDI units, such as naphthodiperylenetetraimide (NDP), are proven beneficial to increasing the regularity of polymer backbones and enhancing the molecular packing in blend films, thus optimizing the active-layer morphology and improving the device performance. However, most investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 47 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Consequently, when paired with PTB7Th as the donor and utilizing 1-chloronaphthalene (CN) as a solvent additive, PTP-TT achieves a PCE of ∼7.04%. 78 Tetraphenylethylene (TPE) features inherently twisted configurations and is connected to four PDI2 (dimer) units, resulting in TPE-4PDI2. When paired with PTB7-Th, TPE-4PDI2 exhibits a PCE of 7.10%.…”
Section: Research and Advancement In Pdi-based Solar Cellsmentioning
confidence: 99%
“…Consequently, when paired with PTB7Th as the donor and utilizing 1-chloronaphthalene (CN) as a solvent additive, PTP-TT achieves a PCE of ∼7.04%. 78 Tetraphenylethylene (TPE) features inherently twisted configurations and is connected to four PDI2 (dimer) units, resulting in TPE-4PDI2. When paired with PTB7-Th, TPE-4PDI2 exhibits a PCE of 7.10%.…”
Section: Research and Advancement In Pdi-based Solar Cellsmentioning
confidence: 99%
“…28 Subsequently, the PCE was increased to 3.04% when choosing PBDTTT-C-T as the donor in 2014 and then was continuously maximized to 3.49% when matched with donor BDDT in 2017. 29,30 Assisted by the design idea of the welldeveloped PDs, substantial efforts devoted to constructing donor-acceptor (D-A) structured alternating conjugated polymers (CPs) via coupling with numerous electron-rich units, i.e., vinylene (V), 26,27,31 fluorene (F), [31][32][33] carbazole (Cz), 31,32 benzo[1,2-b:4,5-b 0 ]dithiophene (BDT), [33][34][35][36] naphtho[1,2-b:5,6b 0 ]dithiophene (NDT), 36 thiophene (T), 25,31,37,38 selenophene (Se), 37,39 tellurophene (Te), 40 bithiophene (2T), [41][42][43] thieno[3,2b]thiophene (TT), [36][37][38] thienylenevinylene (TVT), 44 31 and so on. Apparently, among these PDI-based D-A type CPs, thiophene, tellurophene and vinylene building blocks possessing relatively small volume cubage exhibited an excellent PCE of over 6% (Table S1, ESI †).…”
Section: Introductionmentioning
confidence: 99%
“…Among n-type polymers, those based on naphthalene diimide (NDI) and perylene diimide (PDI) are an important series that show good performances in all-polymer solar cells [18][19][20][21][22]. Performances of OSCs combining PDI-based D-A acceptor polymers with adequate p-type polymers achieved power conversion efficiencies (PCE) up to 7% [23]. It has been demonstrated that D-A copolymers based on DPP combined with thiophene or selenophene could exhibit a high photoresponse with a tuneable absorption edge from 950 to 1200 nm, allowing PCE from 2.9% to 5.3% [24].…”
Section: Introductionmentioning
confidence: 99%